Biomechanical Investigation of the Osseointegration of Titanium Implants With Different Surfaces Placed With Allogeneic Bone Transfer - Ozcan, Erhan Cahit; Aydin, Melek Atille; Dundar, Serkan; Tanrisever, Murat; Bal, Ali; Karasu, Necmettin; Kirtay, Mustafa (Lippincott Williams & Wilkins, 2024)
Allogeneic grafts can be preferred to autogenous grafts in plastic and oral-maxillofacial surgery for vertical and horizontal bone deficiencies. Implant surface properties are an important factor in osseointegration. This study aims to evaluate the osseointegration levels of titanium implants with machined, sand-blasted, and acid-etched (SLA) and resorbable blast material (RBM) surfaces placed together with allogeneic bone tissue transplantations obtained from the tibia bone using biomechanical method. Twenty-five female Sprague-Dawley rats were included in the study. The rats were divided into groups in which machined (n=7), SLA (n=7), and RBM (n=7) surface implants were placed with the transplantation of bone taken from the tibia. Four rats (both left and right tibias) were used as donors. Grafts and implants were surgically placed in the corticocancellous part of the metaphyseal area of the tibia bones of rats. At the end of the 4-week experimental setup, all rats were killed, and the implants and surrounding bone tissue were subjected to biomechanical reverse torque analysis (N/cm). Sand-blasted acid-etched surface implants were observed to have higher biomechanical osseointegration levels than RBM and machined surface implants (P<0.05). No statistical difference could be detected between the RBM and machined surface implants (P>0.05). On the basis of the limited results of this study, it can be concluded that the osseointegration levels of SLA surface implants placed with allogeneic bone transplantation may be better than those of machined and RBM surface implants.
Keywords: Allogeneic bone transfer; bone-implant connection; bone-implant contact; bone transplantation; implant surfaces; osseointegration